2023
DOI: 10.3390/pathogens12111358
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Hetero-Pathogenic and Diarrheagenic Escherichia coli Pathotypes in Diarrheic Children under Five Years and Exposure Environment in Ogun State, South-West Nigeria

Tosin Segun Ogunbiyi,
Olanrewaju Emmanuel Fayemi,
Gabriel Bidemi Akanni
et al.

Abstract: Background: Diarrheagenic Escherichia coli (DEC) is one of the most common etiological agents of moderate-to-severe diarrhea in Low- and Middle-Income Countries (LMICs). Therefore, determining the source(s) of DEC in index cases and exposure environment is important for developing a prevention strategy. The current study aims to investigate the prevalence of DEC among children under 5 years and their exposure environment in Ogun State, Nigeria. Methods: Samples from 228 diarrheic children and their exposure en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The result was higher than a study conducted in India [ 84 ], which found a detection rate of 3.8%. In other studies, hybrid pathotypes were identified among children suffering from diarrhea with a corresponding rate of 6% in Pakistan [ 76 ], 3.9% in Nigeria [ 85 ], and 14% in Ethiopia [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result was higher than a study conducted in India [ 84 ], which found a detection rate of 3.8%. In other studies, hybrid pathotypes were identified among children suffering from diarrhea with a corresponding rate of 6% in Pakistan [ 76 ], 3.9% in Nigeria [ 85 ], and 14% in Ethiopia [ 65 ].…”
Section: Discussionmentioning
confidence: 99%